2013
DOI: 10.1002/hyp.9811
|View full text |Cite
|
Sign up to set email alerts
|

A variable source area for groundwater evapotranspiration: impacts on modeling stream flow

Abstract: Abstract:Evapotranspiration (ET) plays a crucial role in catchment water budgets, typically accounting for more than 50% of annual precipitation falling within temperate deciduous forests. Groundwater ET is a portion of total ET that occurs where plant roots extend to the capillary fringe above the phreatic surface or induce upward movement of water from the water table by hydraulic redistribution. Groundwater ET is spatially restricted to riparian zones or other areas where the groundwater is accessible to pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 55 publications
3
12
0
Order By: Relevance
“…The contribution of riparian ET to water budgets was especially noticeable during the dry period of the year, when it contributed as much as 19% to daily catchment depletions. These values are similar to those estimated for other catchments with AI = 0.6-0.8 (Folch and Ferrer, 2015;Tsang et al, 2014;Wine and 350 Zou, 2012;Yeh and Famiglietti, 2008) and suggest that computations of catchment water budgets neglecting riparian ET will overestimate catchment water resources.…”
Section: Influence Of Riparian Et On Stream Flow and Catchment Water supporting
confidence: 80%
See 1 more Smart Citation
“…The contribution of riparian ET to water budgets was especially noticeable during the dry period of the year, when it contributed as much as 19% to daily catchment depletions. These values are similar to those estimated for other catchments with AI = 0.6-0.8 (Folch and Ferrer, 2015;Tsang et al, 2014;Wine and 350 Zou, 2012;Yeh and Famiglietti, 2008) and suggest that computations of catchment water budgets neglecting riparian ET will overestimate catchment water resources.…”
Section: Influence Of Riparian Et On Stream Flow and Catchment Water supporting
confidence: 80%
“…This value is consistent with previous studies showing that riparian ET can reduce the amount of water entering to streams by 30-100% (Dahm et al, 2002;Folch and Ferrer, 2015;Kellogg et al, 2008;Lupon et al, 2016). Previous models have suggested that the transpiration process from saturated riparian zones is essential to successfully represent the annual water balance of water-limited 345 catchments (Medici et al, 2008;Tsang et al, 2014). On an annual basis, our simulations indicate that riparian ET can account for ~ 7% of annual catchment depletions at Font del Regàs (Table 4).…”
Section: Influence Of Riparian Et On Stream Flow and Catchment Water mentioning
confidence: 57%
“…Ongoing hydrologic monitoring provided stream discharge and total suspended solid (TSS) data. Since 1998, stream stage has been measured every 15 min with Telog and MiniTroll pressure transducers and converted to discharge based on rating equations developed and evaluated monthly with a flow meter (Newbold et al, ; Tsang et al, ). TSS was determined gravimetrically on automatically collected samples taken at the Stroud Water Research Center approximately hourly over individual storm hydrographs as well as grab samples taken at least monthly during baseflow (Aufdenkampe et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Tsang et al (2014) showed that adding a better evapotranspiration scheme in a widely used runoff model improves streamflow predictions. Conradt et al (2013), who compared three different strategies for deriving sub-basin aET, affirmed that incorporating spatial variation of aET in a semi-distributed model increases its robustness.…”
Section: G Ruiz-pérez Et Al: Calibration Of a Parsimonious Distribumentioning
confidence: 99%